Outdoor air quality sulphur dioxide in Istanbul - (:unkn) unknown (BULGARIAN ACAD SCIENCE, 2017)
Oxidation of sulfur dioxide (SO2) may form various atmospheric air pollutants, which is caused by natural processes or human activity. Chemical composition of the atmosphere and biosphere can change depending on the efficiency of the oxidation processes. Atmospheric gases like H2SO4 released by the oxidation of SO2 is naturally removed from the atmosphere through oxidizing chemical reactions. Human activity can increase the amount of gases in the atmosphere, therefore it can affect the oxidation capacity. As a result of OH reaction, these gases are destroyed and removed from the atmosphere. OH reaction converts SO2 to sulfuric acid H2SO4. Rain carries the sulfuric acid to biosphere or hydrosphere. Free radicals are found in the atmosphere in small amounts, however, they rapidly react with other substances and thus spread through the atmosphere. SO2 is one of the reactive radicals which has an effect on the oxidation processes. It plays an important role in the balance of atmospheric composition. This study evaluates the SO2 values in Kandilli, Sultanbeyli and Umraniye districts in Istanbul that was measured by Istanbul Marmara Clean Air Centre between March 1, 2013 and April 30, 2016. According to the measurements, the level of SO2 was below the minimum level recommended by Turkish Government. Accordingly, it has been determined that the air quality was satisfactory; and the air pollution poses little or no risk to human health. In addition, temperature was found to have a significant impact on SO2 compared to wind velocity and humidity. It was observed that SO2 concentrations increased in winters compared to other seasons. SO2 mean concentrations were lower in Istanbul compared to other countries.
Keywords: outdoor air quality; SO2; oxidation; Istanbul; DAILY MORTALITY; POLLUTION; SO2